Semiautomatic whole-lesion apparent diffusion coefficient assessment for early prediction of liver tumor response to radioembolization - Rathmann, Nils-Andreas; Budjan, Johannes; Attenberger, Ulrike; Kostrzewa, Michael; Sadick, Maliha; Schönberg, Stefan; Diehl, Steffen J. (Anticancer research, 2016)
Aim: To evaluate volume-based apparent diffusion coefficient (ADCVOL) values for early prediction of therapy response after radioembolization (RE) of primary and secondary liver malignancies using a semiautomatic, image analysis software prototype. Patients and Methods: In a retrospective analysis, 74 target lesions were assessed in terms of therapy response 1 month after RE using magnetic resonance imaging. Changes of the diameter of the target lesions, the mean ADC value in a representative single-slice region of interest (ADCROI) and mean ADCVOL were correlated. Results: The median progression-free interval (PFI) of patients overall was 3.5±5.9 months. PFI in patients with an ADCVOL increase was statistically significantly longer than in patients with an ADCVOL decrease (mean PFI=6.5 vs. 2.5 months; p=0.0374). No correlation between PFI and early changes in lesion diameter or ADCROI was found. Conclusion: Semiautomatic, software-based ADC volume measurements seem to offer a clinically valuable parameter for early prediction of therapy response in patients after RE.
Gesehen am 25.06.2019